Impact of Early Empiric Antibiotic Regimens on the Gut Microbiota in Very Low Birth Weight Preterm Infants: An Observational Study - Chang, Hung-Yang; Chiang Chiau, Jen-Shiu; Ho, Yu-Hsuan; Chang, Jui-Hsing; Tsai, Kun-Nan; Liu, Chia-Yen; Hsu, Chyong-Hsin; Lin, Chia-Ying; Ko, Mary Hsin-Ju; Lee, Hung-Chang (Frontiers in Pediatrics, 2021)
Frequent use of antibiotics in preterm infants disturbs their gut microbial balance. In this preliminary observational study, we investigated the effect of different antibiotic regimens, administered during the first week of life, on microbial composition and diversity in very low birth weight (VLBW) preterm infants. We performed fecal sampling of breastfed VLBW infants on days 7, 14, and 30. After excluding stool samples from infants who received probiotics or who were administered antibiotics beyond the age of 7 days, we compared gut microbiota profiles between infants receiving a combination of ampicillin and gentamicin for 3 days (AG group, n = 10) and those receiving a combination of ampicillin and cefotaxime for 7 days (AC group, n = 14) using 16S ribosomal DNA community profiling. We also assessed the changes over time in each group. Compared to the AG group, Enterococcus species were significantly more abundant in the AC group (P = 0.002), especially in 7-day samples (12.3% vs 0.6%, respectively, P = 0.032). No difference was observed at phylum and genus level over time within each group. Species richness in the AC group decreased significantly in the 14-day (P = 0.038) and 30-day (P = 0.03) samples compared to that in the 7-day sample. The same was observed for microbial evenness; in contrast, no significant difference in Shannon index and beta-diversity was detected between the two groups. Controlling for relevant confounding variables did not change the results. In conclusion, different antibiotic regimens affect the early development of gut microbiota in VLBW preterm infants. Prolonged use of ampicillin and cefotaxime might result in overabundance of Enterococcus. However, given that no significant differences were observed in 1-month samples, bacterial genera appear to continue colonizing the gastrointestinal tract despite previous exposure to antibiotics. The clinical relevance of these findings should be elucidated by further studies.